Tumor hypermetabolism confers resistance to immunotherapy. (October 2020) - Liu, Arthur; Curran, Michael A.
Abstract: Advances in our understanding of tumor immune biology and development of cancer immunotherapies have led to improved outcomes for patients that suffer from aggressive cancers such as metastatic melanoma. Despite these advances, a significant proportion of patients still fail to benefit, and as a result, attention has shifted to understanding how cancer cells escape immune destruction. Of particular interest is the metabolic landscape of the tumor microenvironment, as recent studies have demonstrated how both competition for essential nutrients and depletion of specific amino acids can promote T cell dysfunction. Here, we will discuss the major energetic pathways engaged by both T cells and cancer cells, metabolic substrates present in the tumor microenvironment, and emerging therapeutic strategies that seek to improve T cell metabolic fitness and bolster the antitumor immune response.